FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA TIDAK MENGGUNAKAN BANK SYARIAH SEBAGAI TRANSAKSI UTAMA - Brahmana, Meilisa Nina Sari Br (Islamic Economics and finance in Focus, 2022)
In Indonesia, banking is divided into two forms, namely conventional bank and Islamic bank. The existence of Islamic banks is a solution for people who want to make transactions without usury. Because usury is prohibited in Islam, however, there are still many people who are more satisfied with using conventional banks. Indonesia has a population of 86.80% adheres to Islam but the market share of Islamic banks is only 6.5%. So this is what makes this research. This study aims to determine what factors influence students not to use Islamic banks as the main transaction from the point of view of those who have used Islamic banks. This study uses a quantitative approach with logistic regression analysis. The sampling method used was non-probability sampling with purposive sampling technique. The sample from this student there are 90 students of the Faculty of Economics and Business Universitas Brawijaya class of 2018 who use Islamic banks not as the main transaction and as the main transaction. The results of the study explain that the variables of price, service, knowledge, and location partially have a significant effect on students decision not to use Islamic banks as the main transaction in making transactions.